Identification of rice cornichon as a possible cargo receptor for the Golgi-localized sodium transporter OsHKT1;3 - Rosas-Santiago, Paul; Lagunas-Gómez, Daniel; Barkla, Bronwyn J; Vera-Estrella, Rosario; Lalonde, Sylvie; Jones, Alexander; Frommer, Wolf B; Zimmermannova, Olga; Sychrová, Hana; Pantoja, Omar (Journal of experimental botany, 2015)
Membrane proteins are synthesized and folded in the endoplasmic reticulum (ER), and continue their path to their site of residence along the secretory pathway. The COPII system has been identified as a key player for selecting and directing the fate of membrane and secretory cargo proteins. Selection of cargo proteins within the COPII vesicles is achieved by cargo receptors. The cornichon cargo receptor belongs to a conserved protein family found in eukaryotes that has been demonstrated to participate in the selection of integral membrane proteins as cargo for their correct targeting. Here it is demonstrated at the cellular level that rice cornichon OsCNIH1 interacts with OsHKT1;3 and, in yeast cells, enables the expression of the sodium transporter to the Golgi apparatus. Physical and functional HKT-cornichon interactions are confirmed by the mating-based split ubiquitin system, bimolecular fluorescence complementation, and Xenopus oocyte and yeast expression systems. The interaction between the two proteins occurs in the ER of plant cells and their co-expression in oocytes leads to the sequestration of the transporter in the ER. In the yeast cornichon mutant erv14, OsHKT1;3 is mistargeted, preventing the toxic effects of sodium transport in the cell observed in wild-type cells or in the erv14 mutant that co-expressed OsHKT1;3 with either OsCNIH1 or Erv14p. Identification and characterization of rice cornichon as a possible cargo receptor opens up the opportunity to improve our knowledge on membrane protein targeting in plant cells.
Keywords: Animals; biologický transport; Golgiho aparát; Sequence Analysis, Protein; Sodium; Golgi; Membrane Transport Proteins; rýže (rod); sekvence aminokyselin; Plant Proteins; membránové transportní proteiny; Oryza; Xenopus; Molecular Sequence Data; Endoplasmic Reticulum; Golgi Apparatus; Amino Acid Sequence; mapování interakce mezi proteiny; protein–protein interaction.; rostlinné proteiny; Biological Transport; endoplasmic reticulum; molekulární sekvence - údaje; Protein Interaction Mapping; OsHKT1; 3; sodík; Sequence Alignment; Cation Transport Proteins; proteiny přenášející kationty; zvířata; Cornichon; endoplazmatické retikulum; sekvenční analýza proteinů; sekvenční seřazení